Campo experimental de Cruz Alta (RS): interpretação de provas de carga estáticas em estacas escavadas em solo potencialmente colapsível - Hillesheim, Luís Henrique (2024)
This research presents the evaluation of a set of 20 static load tests, carried out on piles measuring 3.00m and 6.00m in length, 0.30m in diameter, bored in laterite and possibly collapsible soil, carried out in the Experimental Field, in the city of Cruz Alta, RS. Of the static load tests analyzed, 16 of them belonged to the database and 4 of them were increased during this research, representing results from bored piles with a length of 6.00m in flooded soil conditions. In the analyzes carried out, it is demonstrated that the piles excavated from the experimental field, when evaluated in natural humidity conditions and in the first PCE, function as lateral friction piles, with a low presence of tip resistance. On average, assessment using the stiffness method indicates that 3.00m bored piles can resist up to 100kN by lateral friction and 6.00 m piles can resist up to 200kN by lateral friction. On the other hand, the tip resistance, when it is viable to manifest, occurs with the piles presenting settlements in the order of conventional “rupture”, when executing excavated piles with reinforcement at the crushed stone tip this effect is attenuated. The value of lateral friction developed when the soil is at natural humidity indicates that the load capacity of the piles is above average, possibly due to the laterite character of the clays in the region. However, when the soil is flooded, there is a tendency to reduce the load capacity of the piles in the PCE test (reloads) of an average of 31% for conventional 3.00m tipped piles, 39.5% for those with reinforced tip of 3.00m and 28% for the piles and 6.00m. The separation of lateral friction and tip resistance cannot be carried out in these cases, as the presence of residual loads impacts the observations in the stiffness graph of the bored piles, with the straight line leading to zero stiffness describing the lateral friction at failure plus the effect of residual load trapped at the pile tip.